Konstruksi Hukum Peran Ahli dalam Forum Alternatif Penyelesaian Sengketa (APS) di Indonesia - Shyavara Aisyah (Lembaga Pengembangan Kinerja Dosen, 2025)
The role of experts in the Alternative Dispute Resolution (APS) forum in Indonesia has a strategic position in bridging the technical and legal aspects that are often at the core of the problem in a dispute. The presence of experts serves to provide objective and professional opinions that can strengthen the arguments of the parties, as well as speed up the dispute resolution process efficiently. Juridically, the role of experts has been recognized in Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, and strengthened by the principle of freedom of contract in Article 1338 of the Civil Code. Although expert opinions are not always binding, their contributions are often used as the basis for important consideration by mediators or arbitrators in decision-making. In addition to being a provider of expert opinions, this role is also able to bridge the gap of understanding between technical and legal aspects that are often difficult to understand by the parties or even by the mediator himself. In practice, expert involvement can provide insight into complex issues, such as in construction, medical, information technology, or environmental cases, that require specialized expertise. Therefore, the presence of experts not only strengthens the legal argument, but also provides crucial scientific validity. However, the challenge faced is the lack of detailed technical arrangements related to qualifications, codes of conduct, and mechanisms for expert involvement in the APS. This can pose a risk of subjectivity and potential conflicts of interest. For this reason, a more comprehensive regulatory development is needed to ensure that the role of experts in APS can be carried out optimally, professionally, and fairly, so as to increase public trust in the dispute resolution mechanism outside the court.